Mobilitätsbericht 2011. Offenbach am Main. - (:unkn) unknown (My University, 2012)
Since the beginning of 2008, the local passenger transport associations of the city and the district of Offenbach offer enterprises within their transport sector a special and free service: the operational mobility management. Therewith, LNO, the local transport association of Offenbach, and KVG, the districts Kreis-Verkehrs-Gesellschaft, pursuit ambitious aims: they want to conciliate the triad of mobility, economic growth and environmental protection. To achieve this target, they aim at introducing the growing group of commuters to ecomobility by establishing new and attractive mobility-possibilities with support of municipality and employers.
From triad to harmony with mobility management.
Keywords: Verkehr; Stadtverkehr; Wirtschaftsentwicklung; Mobilität; Verkehrsmittelwahl; Verkehrsverhalten; Verkehrspolitik; Mobilitätsmanagement